Floricane Blackberry Pruning Guide for Florida - Muhammad A. Shahid; Ali Sarkhosh (EDIS)
This article aims to provide a general overview of growth habits, fruiting patterns, and pruning requirements/timing for county and state Extension faculty, growers, homeowners, and students interested in growing floricane blackberries in Florida. Written by Muhammad A. Shahid and Ali Sarkhosh, and published by the UF/IFAS Horticultural Sciences Department, March 2023.